Sosialisasi Higiene Sanitasi Makanan dan Pengelolaan Bahan Kimia pada Pekerja UMKM Kota Palembang - Arie Anggara; Doly Nofiansyah; Hala Haidir (I-Com: Indonesian Community Journal, 2025)
The issue of food hygiene, sanitation, and chemical management in Palembang, based on previous research, shows low hygienic practices among food handlers in the Workers of Small and Medium Enterprises (SMEs) sector, such as non-compliance with handwashing and failure to use aprons and gloves. This is consistent with laboratory findings that identified Escherichia coli contamination in several food and beverage samples from SMEs, exceeding established food safety limits. This activity aims to socialize food sanitation, hygiene, and chemical management among workers of SMEs in Palembang City. The methods used are preparation of socialization activities, implementation of socialization activities, and evaluation of activities. Post-test results showed that there was an increase in knowledge related to food sanitation hygiene and chemical management among food SMEs workers, namely 12 participants (60%) had "very good" knowledge. By carrying out socialization activities on food sanitation hygiene and chemical management among Palembang City SMEs workers, it is hoped that it can increase the productivity and good image of Palembang City food SMEs workers.